Disability Research and Policy : Current Perspectives. (Taylor & Francis, 2005)
This book is based on research and scholarship produced by the Meyerson Disability Research Project (MDRP) at the University of Arizona. Its chapters are divided into two major sections: 1) Disability Research Areas and 2) Disability Policy Areas. The fi.